2015
DOI: 10.1007/s11745-015-4062-4
|View full text |Cite
|
Sign up to set email alerts
|

U18666A Treatment Results in Cholesterol Accumulation, Reduced Na+, K+‐ATPase Activity, and Increased Oxidative Stress in Rat Cortical Astrocytes

Abstract: The objective of this study was to determine the effect of U18666A, an inhibitor of cholesterol synthesis and its intracellular transport, on oxidative stress parameters in cortical astrocytes cultured from Wistar rats (0-3 days old). The cultures were incubated with U18666A (0.25 µg/mL) for 48 h, conditions that are considered ideal to mimic Niemann-Pick type C disease. A variety of indicators of oxidative stress were measured. U18666A treatment increased cholesterol 2-fold in treated compared to control astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The treatment with U18666A resulted in an accumulation of cholesterol as expected, but moreover we observed gliosis in the control cells, demonstrated by a significantly increased number of GFAP + /vimentin + cells, accompanied by a reduced amount of phosphorylated GFAP and vimentin. Recent studies described U1866A induced cholesterol accumulations in rat astrocytes influencing the metabolic pathway of these cells [ 56 , 57 ], but effects in regards of gliosis were not topic of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment with U18666A resulted in an accumulation of cholesterol as expected, but moreover we observed gliosis in the control cells, demonstrated by a significantly increased number of GFAP + /vimentin + cells, accompanied by a reduced amount of phosphorylated GFAP and vimentin. Recent studies described U1866A induced cholesterol accumulations in rat astrocytes influencing the metabolic pathway of these cells [ 56 , 57 ], but effects in regards of gliosis were not topic of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since the function of the NPC2 protein is to control intracellular free cholesterol homeostasis [ 19 , 20 ], we next determined whether direct free cholesterol accumulation in HSCs would cause the same response toward PDGF-BB treatment like the NPC2 knockdown HSCs. U18666A, an inhibitor of free cholesterol transport, is a positive control to induce free cholesterol accumulation [ 26 , 27 , 28 , 29 ]. As shown in Figure 1 B,C, on the right, similar results were observed where U18666A-treated HSCs had a significant increase in cell proliferation when compared with the control, while PDGF-BB treatment did not influence the free cholesterol levels in HSCs ( Figure 1 D, left).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, from our previous research, we found that knockdown NPC2 in HSC-T6 cells would increase 20% free cholesterol accumulation [ 24 ]. Since U18666A is a specific drug that induces free cholesterol sequestration in late endosomes/lysosomes and mimics an NPC phenotype [ 27 , 28 , 29 ], the efficiency of U18666A showed a more than 50% increase in cholesterol accumulation when compared to the control [ 26 , 58 ]. Together, these results suggest that increased TLR4 expression in free cholesterol accumulated HSCs may be a key factor in responding to LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has implied that inhibition of LSS causes secondary apoptosis in neurons due to increase in reactive oxygen species (ROS) [ 30 ]. It also observed a decreased catalase (CAT) and superoxide dismutase (SOD) activity in astrocytes after inhibiting LSS activity, which causes the dysfunction of lipid metabolism in the cerebral cortex [ 31 , 32 ]. As a result, we speculate that LSS resists oxidation and after inhibiting LSS activity, oxidative stress increases and leads to dysfunctional lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%